Recent Advances on Biomass-Derived Carbon Materials-Based Electrochemical Sensors - Dacheng Wang; Yan Deng; Xiaowei Liu; Baoli Wang; Feng Yang (Molecules, 2025)
Biomass-derived carbon materials (BDCMs) have garnered numerous research interests due to their conspicuous electrochemical merits, which makes them promising candidates for electrode modification materials in electrochemical sensors. This review focuses on the recent progress in BDCM-based electrochemical sensors. We summarize the main synthesis methods and properties of BDCMs and their electrochemical sensing applications in the detection of environmental pollutants, drugs, and biomolecules. This review also emphasizes the advantages and disadvantages of each preparation method, as well as the limitations in detecting the target substance. Furthermore, this review discusses the current challenges and future prospects for advancing biomass-derived carbon materials-based electrochemical sensors.